The danube dynamics of the real estate transfer tax - Radka MacGregor Pelikánová; Petra Jánošíková (DANUBE: Law, Economics and Social Issues Review, 2017)
The real estate transfer tax was introduced by the Habsburgs in the 19th century and has remained an integral part of the tax system of almost all countries historically belonging to their Danube monarchy. One century after the monarchy's collapse, their common roots as well as national particularities can be observed. The goal of this paper is to confirm or reject the proposed hypothesis that the real estate transfer tax and its rate in post-Danube monarchy countries reflects more general public policies and preferences than neutral fiscal needs as suggested by GDP, GDP/capita, government debt/GDP, tax revenue/GDP, etc. The critical, genesis reflecting and comparative meta-analysis of the information about the dynamics of the evaluating regimes of the real estate transfer tax leads to the conclusion in the form of the confirmation of the proposed hypothesis, especially regarding the Czech Republic, making real estate transfer tax conceptually more a political than a fiscal instrument and posing a set of Socratic style questions inviting further research.
Keywords: 330; Real Estate Transfer Tax; Tax Law; Habsburg Monarchy; State Budget